The Size and Performance of Public Sector Activities in Europe - Heinz Handler; Bertrand Koebel; Philipp Reiss; Margit Schratzenstaller (Austrian Institute of Economic Research (WIFO), 2005)
The obvious difference in the economic performance of countries has led to the question why some countries are so much wealthier than others, and whether the size, the structure, and the organisation of the public sector contribute to cross-country income and growth gaps. Public sector activities may have an effect on overall productivity and growth via two channels: directly by the level and changes of productivity within the public sector, and indirectly by triggering off productivity changes in private production. This paper is concerned with the former aspect. It provides an overview of the size and the structure of the public sector in Europe and compares it with the US and Japan. This is related to the more recent empirical literature on public sector performance. After reviewing some of the measurement issues related to public services, the evidence on the size of government and its performance is analysed. The results on industrial countries are not fully conclusive, but seem to attribute more efficiency to smaller rather than to larger governments. Public sector reforms to consolidate the size of government are therefore likely to enhance the sector's own productivity and thereby positively contribute to overall economic performance.
Keywords: 330; Öffentlicher Sektor; Öffentliche Ausgaben; Produktivität; Vergleich; EU-Staaten; USA; Japan